Posture control after prolonged exercise - Lepers, R.; Bigard, A. X.; Diard, J. -P.; Gouteyron, J. -F.; Guezennec, C. Y. (European Journal of Applied Physiology, 1997)
The perturbations of equilibrium after prolonged exercise were investigated by dynamic posturography on nine well-trained subjects (four athletes and five triathletes). The results showed that the ability to maintain postural stability during conflicting sensory conditions decreased after exercise, with some differences depending on the kind of exercise.